Hexagonal boron nitride powder, resin composition, resin sheet, and method for producing hexagonal boron nitride powder

JP2026166591APending Publication Date: 2026-10-14TOKUYAMA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025059622
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0017】 本発明の六方晶窒化ホウ素粉末により、優れた熱伝導性と電気絶縁性を備える樹脂シートを容易に形成できる。それにより、前記樹脂シートを、半導体や電子機器に使用すると、優れた放熱性と電気絶縁性を発揮し、放熱性能および信頼性を大幅に向上させることが容易になる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166591000001
    Figure 2026166591000001
  • Figure 2026166591000002
    Figure 2026166591000002
Patent Text Reader

Abstract

The present invention provides a hexagonal boron nitride powder that ensures high thermal conductivity in resin sheets while suppressing localized decreases in dielectric breakdown voltage. [Solution] It contains hexagonal boron nitride aggregated particles, with an average particle size of 30-80 μm and a specific surface area of ​​1.8-4.0 m². 2 Hexagonal boron nitride powder with a density of / g, an oil absorption capacity of 55-85 ml / 100g, and fewer than 15 foreign particles per kg with a major diameter of 50 μm or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to hexagonal boron nitride powder, resin compositions, resin sheets, and a method for producing hexagonal boron nitride powder. [Background technology]

[0002] Hexagonal boron nitride exhibits excellent electrical insulation, thermal conductivity, and thermal stability, and is used as a filler in resin sheets used in semiconductors and electronic devices. In recent years, with the miniaturization and increased power of semiconductors and electronic devices, there has been a demand for even higher thermal conductivity and electrical insulation in these resin sheets.

[0003] To achieve high thermal conductivity, hexagonal boron nitride powder containing aggregated hexagonal boron nitride particles is required. Normally, hexagonal boron nitride forms flaky primary particles due to its crystal structure, and when these particles are filled into a resin sheet, for example, they orient themselves in the direction of the resin sheet's surface. This reduces the thermal conductivity in the thickness direction of the resin sheet, but the inclusion of aggregated particles can reduce this thermal anisotropy. To obtain hexagonal boron nitride powder containing a large amount of such aggregated particles and exhibiting a high thermal conductivity-improving effect, the manufacturing process of hexagonal boron nitride powder requires long nitriding reactions and re-calcination treatments.

[0004] For example, Patent Document 1 discloses a hexagonal boron nitride powder consisting of aggregated particles that exhibits excellent thermal conductivity and electrical insulation when used as a filler. Furthermore, the production of this hexagonal boron nitride powder requires a re-calcination process.

[0005] Furthermore, from the viewpoint of achieving a high level of electrical insulation of the resin sheet, it is desirable to use hexagonal boron nitride powder with fewer impurities. In particular, since colored impurities containing carbon and metal elements may be conductive, when hexagonal boron nitride powder is used, for example, as the resin sheet, there is a risk that the dielectric strength may decrease locally in the areas where colored impurities are present. In order to avoid impairing the stability of the dielectric strength, it is required that such impurities be highly removed from the hexagonal boron nitride powder.

[0006] Under these circumstances, Patent Document 2 discloses hexagonal boron nitride powder in which the colored particles containing carbon are reduced by focusing on unreacted carbon in the raw material and allowing it to react sufficiently during the calcination process. Patent Document 3 discloses hexagonal boron nitride powder in which the colored foreign matter is highly removed by focusing on unreacted carbon components mainly derived from the raw material, by-products such as complex oxides, or metallic foreign matter contained in the raw material, and performing acid washing, magnetic separation, suction removal, etc., during the manufacturing process. [Prior art documents] [Patent Documents]

[0007] [Patent Document 1] Patent No. 7588527 [Patent Document 2] International Publication No. 2022 / 071245 [Patent Document 3] International Publication No. 2024 / 225208 [Overview of the project] [Problems that the invention aims to solve]

[0008] As described above, when hexagonal boron nitride powder is used as a resin sheet, it is desirable to remove foreign matter to a high degree in order to achieve a high level of electrical insulation. Therefore, the present inventors attempted to remove foreign matter to a high degree when manufacturing the hexagonal boron nitride powder described in Patent Document 1 using the methods described in Patent Documents 2 and 3. As a result, even in hexagonal boron nitride powder containing many aggregated particles, colored and black foreign matter could be removed to the same extent as in Patent Documents 2 and 3, but a problem was found in that localized insulation defects occurred when it was made into a resin sheet (see, for example, Comparative Example 3).

[0009] Therefore, the present invention aims to provide a hexagonal boron nitride powder that can suppress a localized decrease in dielectric breakdown voltage while ensuring high thermal conductivity in a resin sheet. [Means for solving the problem]

[0010] The inventors of the present invention have found that the cause of the aforementioned localized decrease in dielectric strength is fibrous foreign matter. Further investigation into this fibrous foreign matter revealed that it contains carbon fibers derived from the heat insulating material used in the manufacturing equipment, and as mentioned above, it is thought that this is introduced during the manufacturing process through prolonged nitriding reactions and re-calcination treatments. Therefore, it is unavoidable to avoid contamination in the production of hexagonal boron nitride powder containing a large amount of aggregated particles, such as that described in Patent Document 1.

[0011] On the other hand, the methods for removing foreign matter described in Patent Documents 2 and 3 make it difficult to remove such fibrous foreign matter.

[0012] Firstly, Patent Document 2 describes a method for reducing foreign matter in which carbon in the raw material is sufficiently reacted during the firing process. However, this method cannot remove fibrous foreign matter derived from highly heat-resistant insulating materials, and because it involves three stages and a long firing time, the risk of contamination by the aforementioned fibrous foreign matter is higher.

[0013] Next, Patent Document 3 describes a method for highly removing colored foreign matter by performing pickling and magnetic separation treatments on hexagonal boron nitride powder to reduce foreign matter, followed by suction removal at the end of the manufacturing process. However, fibrous foreign matter mainly consists of carbon fibers and cannot be removed by the aforementioned pickling and magnetic separation treatments. Furthermore, in the suction removal method, the object to be measured is leveled to a thickness of about 50 μm and placed on a belt-shaped measuring section, and the object to be measured is observed from above to remove any detected colored foreign matter larger than 50 μm by suction. Although the major diameter of the fibrous foreign matter is 50 μm or more, because it is fibrous, it is easily deformed, such as bending, making it difficult to maintain a size of 50 μm or more within the object to be measured. Moreover, because it is fibrous, it is rare for the entire fibrous foreign matter to be exposed on the surface of the object to be measured compared to foreign matter with an average particle size of 50 μm or more, and if a part of the fibrous foreign matter is embedded in the boron nitride powder being measured, the size of the observed fibrous foreign matter will be even smaller. Therefore, the method described in Patent Document 3 was unable to effectively remove fibrous foreign matter.

[0014] To solve the above problems, the present inventors conducted diligent research and found that by performing airflow classification under specific conditions during the manufacturing process of hexagonal boron nitride powder, the fibrous foreign matter can be highly effectively removed. As a result, even if fibrous foreign matter is mixed into the hexagonal boron nitride powder due to a long nitriding reaction or re-calcination process to obtain hexagonal boron nitride powder containing a large amount of aggregated particles, it is possible to remove the fibrous foreign matter, leading to the present invention.

[0015] That is, the hexagonal boron nitride powder according to one aspect of the present invention contains hexagonal boron nitride aggregated particles, has an average particle size of 30 to 80 μm, and a specific surface area of ​​1.8 to 4.0 m². 2 This is a hexagonal boron nitride powder with a density of 1 / g, an oil absorption capacity of 55-85 ml / 100g, and fewer than 15 foreign particles per kg with a major diameter of 50 μm or more.

[0016] Further, a method for producing hexagonal boron nitride powder according to one aspect of the present invention includes an oxygen-containing boron compound, a carbon source, an oxygen-containing calcium compound, and boron carbide, wherein the ratio B / C (element ratio) of the B-converted mass in the oxygen-containing boron compound to the C-converted mass of the carbon source is 0.81 to 1.10, and relative to 100 parts by mass of the total amount of the B₂O₃-converted mass of the oxygen-containing boron compound and the C-converted mass of the carbon source, the oxygen-containing calcium compound is 4 to 18 parts by mass in terms of CaO, and relative to 100 parts by mass of the total of the B₂O₃, C and CaO-converted masses of the oxygen-containing boron compound, the carbon source, and the oxygen-containing calcium compound respectively, the boron carbide is 10 to 30 parts by mass, a raw material preparation step of preparing a raw material powder, a reduction nitridation step of heating the raw material powder obtained by the raw material preparation step at a temperature of 1500 to 1900° C. for 2 to 12 hours in a nitrogen atmosphere to obtain crude hexagonal boron nitride powder, a refiring step of refiring the crude hexagonal boron nitride powder obtained by the reduction nitridation step at a temperature of 1850 to 2000° C. for 5 hours or more in a nitrogen atmosphere to obtain untreated hexagonal boron nitride powder, and a classification step of classifying the untreated hexagonal boron nitride powder obtained by the refiring step using an airflow classifier to obtain hexagonal boron nitride powder. This is a method for producing hexagonal boron nitride powder.

Effects of the Invention

[0017] With the hexagonal boron nitride powder of the present invention, a resin sheet having excellent thermal conductivity and electrical insulation can be easily formed. Accordingly, when the resin sheet is used in semiconductors and electronic devices, it exhibits excellent heat dissipation performance and electrical insulation, making it easy to significantly improve heat dissipation performance and reliability.

Modes for Carrying Out the Invention

[0018] Hereinafter, the hexagonal boron nitride powder according to one aspect of the present invention will be described in detail. In the description, the hexagonal boron nitride powder according to one aspect of the present invention may be abbreviated as "the present powder". In addition, in the present specification, "A to B" representing a numerical range means "A or more and B or less" unless otherwise specified.

[0019] The present powder includes hexagonal boron nitride aggregated particles. The aggregated particles are secondary particles constituted by a plurality of primary particles (single particles) of hexagonal boron nitride aggregated together. The aggregated particles contained in the present powder are observed using a known microscopic observation method such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).

[0020] [Hexagonal Boron Nitride Powder] The present powder includes hexagonal boron nitride aggregated particles, and has an average particle diameter of 30 to 80 μm, and a specific surface area of 1.8 to 4.0 m 2 / g, an oil absorption of 55 to 85 ml / 100g, and 15 or less foreign matters with a major axis of 50 μm or more per 1 kg.

[0021] The average particle diameter of the present powder is 30 to 80 μm, preferably 35 to 70 μm, and more preferably 40 to 60 μm. By setting the average particle diameter within the above range, the dispersibility in the resin sheet is improved, and the hexagonal boron nitride powder is densely packed, so that the number of thermal conduction paths increases, and a resin sheet with high thermal conductivity is easily obtained.

[0022] The average particle diameter of the present powder is the median diameter D in the volume-based particle size distribution 50 , and in the examples, the measurement is performed using a laser diffraction / scattering particle size analyzer MT3000 (manufactured by MicrotracBEL).

[0023] In the present powder, the specific surface area is an index of the size of the single particles contained in the present powder. In general, the specific surface area tends to increase as the single particles constituting the aggregated particles are smaller, and the specific surface area tends to decrease as the single particles constituting the aggregated particles are larger, and it is preferable to control the specific surface area within a specific range. The specific surface area of the present powder is 1.8 to 4.0 m 2 / g, preferably 2.2 to 3.8 m 2 / g, more preferably 2.4 to 3.6 m 2The specific surface area is within this range. When the individual particles constituting the aggregated particles are of a size that allows for low interfacial resistance and small voids within the aggregate, it becomes easier to obtain aggregated particles that contribute greatly to improving thermal conductivity, and the effect of this powder on improving the thermal conductivity of the resin composition becomes even greater.

[0024] The specific surface area of ​​this powder was measured using the BET 1-point method, and can be measured using, for example, a Micromeritics Flowsorb III 2310 (product name).

[0025] In this powder, the oil absorption amount is an indicator of the number of voids in the aggregated particles contained in the powder and the degree of development of the structure on the surface of the aggregated particles, and it is desirable to control it within a specific range. The lower the oil absorption amount, the less void there is in the aggregated particles as a whole powder. In this powder, the oil absorption amount is 55 mL / 100 g or more, preferably 65 mL / 100 g or more. When the oil absorption amount is within the above range, the powder contains aggregated particles that contribute greatly to improving thermal conductivity, thus increasing the effect of this powder on improving the thermal conductivity of the resin composition. Also, in this powder, the oil absorption amount is 85 mL / 100 g or less, preferably 80 mL / 100 g or less. When the oil absorption amount is within the above range, the incorporation of solvents that cause void formation and a decrease in dielectric breakdown voltage in the resin composition is reduced as a whole powder, thus increasing the effect of this powder on improving the dielectric breakdown voltage of the resin composition.

[0026] Furthermore, the method for measuring the amount of oil absorbed in this specification is the method compliant with JIS-K6217-4, as shown in the examples described later.

[0027] The number of foreign particles with a major diameter of 50 μm or more in this powder is 15 or less per 1 kg of powder, preferably 10 or less, more preferably 7 or less, and even more preferably 5 or less. By keeping the number of foreign particles with a major diameter of 50 μm or more within the above range, it becomes easier to stably exhibit high dielectric strength when filled into a resin sheet. The lower the number of foreign particles with a major diameter of 50 μm or more, the better; for example, it may be 0.

[0028] The number of foreign particles with a major axis of 50 μm or larger in this powder was measured by preparing a resin sheet using this powder and epoxy resin, and visually inspecting the sheet from the top using a camera while irradiating it with light from the bottom. By using a resin sheet, even if the fibrous foreign particles are embedded in the sheet, they can be seen through the resin, allowing for clear observation and enabling more sensitive measurements compared to measuring the powder as is.

[0029] In this specification, "fibrous foreign matter" refers to an object with a major axis of 50 μm or more and a minor axis of 20 μm or less. With the foreign matter measurement method of the present invention, in addition to the fibrous foreign matter, colored particles described in Patent Document 2 and colored foreign matter described in Patent Document 3 can also be measured.

[0030] Patent Document 2 describes observing the material remaining on a 63 μm sieve using an optical microscope and counting the number of foreign particles. However, because fibrous foreign particles are fibrous, they do not remain on the sieve even if their longest diameter is 63 μm or more, and therefore the measurement method described in Patent Document 2 cannot measure the number of fibrous foreign particles.

[0031] Furthermore, Patent Document 3 observes foreign matter larger than 50 μm using a method similar to the aspiration removal described above, and for the reasons stated above, it is not possible to measure the number of fibrous foreign matter with high sensitivity.

[0032] The compressive fracture strength of this powder is preferably 1.0 MPa or higher, and more preferably 2.0 MPa or higher. The compressive fracture strength is an indicator of the hardness of the aggregates contained in this powder, and it is desirable to control it within a specific range. The higher the compressive fracture strength, the less likely the aggregates are to break down when this powder is mixed with resin. When the compressive fracture strength is within the above range, the aggregates tend not to break down and remain in the resin composition, so orientation within the resin composition can be suppressed, and the effect of this powder on improving the thermal conductivity of the resin composition is greatly increased.

[0033] Furthermore, the compressive fracture strength of this powder is preferably 5.0 MPa or less, and more preferably 4.0 MPa or less. When the compressive fracture strength is within the above range, aggregates containing closed air pores tend to break down when the powder is mixed with the resin, which suppresses the formation of voids in the resin composition and tends to increase the effect of improving the dielectric strength of the resin composition by this powder.

[0034] In this specification, the compressive fracture strength of this powder is measured by the method shown in the examples described later. The compressive fracture strength of this powder can be measured, for example, using the MCT-510 (product name) manufactured by Shimadzu Corporation.

[0035] Furthermore, the amount of metal impurities in the hexagonal boron nitride powder is preferably 50 ppm or less, more preferably 30 ppm or less, and even more preferably 10 ppm or less. By setting the amount of metal impurities within the above range, it is easier to stably exhibit high dielectric strength when filled into a resin sheet, and even when used in other applications, it is easier to stably exhibit the properties of the hexagonal boron nitride powder at a high level. There is no particular lower limit for the amount of metal impurities; the lower the better, but it can be, for example, 0 ppm or more.

[0036] The amount of metal impurities in this powder is the sum of the amounts of Fe, Ca, Al, and Si present. In the examples, the measurement was performed using an ICP emission spectrometer (Thermo Fisher Scientific Co., Ltd.: ICAP6500).

[0037] (Application) Applications of this powder include fillers for resin sheets and raw materials for sintered bodies. Such resin sheets can achieve excellent dielectric strength stability and heat dissipation.

[0038] [Method for producing hexagonal boron nitride powder] The present invention provides a method for producing hexagonal boron nitride powder, which is not particularly limited but includes, for example, a raw material preparation step of preparing a raw material powder containing an oxygen-containing boron compound, a carbon source, an oxygen-containing calcium compound, and boron carbide in specific proportions; a reduction nitriding step of heating the raw material powder obtained in the raw material preparation step at a temperature of 1500 to 1900°C for 2 to 12 hours under a nitrogen atmosphere to obtain crude hexagonal boron nitride powder; a re-calcination step of re-calcining the crude hexagonal boron nitride powder obtained in the reduction nitriding step at a temperature of 1850 to 2000°C for 5 hours or more under a nitrogen atmosphere to obtain untreated hexagonal boron nitride powder; and a classification step of classifying the untreated hexagonal boron nitride powder obtained in the re-calcination step using an air-flow classifier to obtain hexagonal boron nitride powder.

[0039] <Raw material preparation process> The aforementioned raw material preparation step is a process of mixing an oxygenated boron compound, a carbon source, an oxygenated calcium compound, and boron carbide in specific proportions to obtain a raw material powder.

[0040] The ratio B / C (elemental ratio) of the B equivalent mass of the oxygenated boron compound in the raw material powder to the C equivalent mass of the carbon source is 0.81 to 1.10, preferably 0.90 to 1.00. When B / C is within this range, unreacted carbon is less likely to remain in the raw material boron nitride powder, and the proportion of unreacted B2O3 is not excessive, suppressing a decrease in the yield of boron nitride relative to the raw material filling amount and improving productivity.

[0041] Furthermore, with respect to 100 parts by mass of the total amount of the oxygenated boron compound in the raw material powder converted to B2O3 on a B basis and the carbon source converted to C, the oxygenated calcium compound is in an amount of 4.0 to 18.0 parts by mass, preferably 7.0 to 12.0 parts by mass, in terms of CaO on a Ca basis. When the amount of CaO converted to mass is within this range, the boron compound is less likely to volatilize, and the yield is improved. In addition, grain growth of the hexagonal boron nitride powder is suppressed, and the desired aggregated particles are more easily formed.

[0042] The amount of boron carbide is 10 to 30 parts by mass, preferably 15 to 25 parts by mass, per 100 parts by mass of the total amount of B2O3, C, and CaO equivalents of the oxygenated boron compound, the carbon source, and the oxygenated calcium compound. By setting the amount within this range, the amount of hard aggregated particles that contribute greatly to thermal conductivity is increased, improving the effect of this powder on improving the thermal conductivity of the resin composition, and making it less likely for unreacted boron carbide to remain.

[0043] (oxygen-containing boron compound) As the oxygenated boron compound, a compound containing both boron and oxygen atoms may be used. Examples of oxygenated boron compounds include boric acid, boric anhydride, metaboric acid, perboric acid, hypoboric acid, sodium tetraborate, and sodium perborate. Of these, boric acid or boron oxide, which are readily available, may be preferably used.

[0044] (Carbon source) Examples of carbon sources include amorphous carbon such as carbon black, activated carbon, and carbon fiber, as well as crystalline carbon such as diamond, graphite, and nanocarbon, and pyrolytic carbon obtained by thermal decomposition of monomers or polymers. Of these, amorphous carbon, which is highly reactive, is preferred, and carbon black is particularly suitable for use because its quality is industrially controlled. Examples of carbon black include acetylene black, furnace black, and thermal black.

[0045] (Calcium oxygen-containing compounds) Oxygen-containing calcium compounds form complex oxides with oxygen-containing boron compounds, creating high-melting-point complex oxides and preventing the volatilization of oxygen-containing boron compounds. They have also been confirmed to act as catalysts in the direct nitridation reaction of boron carbide.

[0046] (Boron carbide) As the boron carbide, known carbon boron may be used. The particle size of the boron carbide is preferably 30 to 500 μm, more preferably 100 to 300 μm, and even more preferably 150 to 250 μm.

[0047] <Reduction Nitride Process> The reduction nitriding step is a step in which the raw material powder obtained in the raw material preparation step is heated while supplying a nitrogen source to carry out a reduction nitriding reaction. In the reduction nitriding step, the supply of the nitrogen source to the reaction system can be established by known means. For example, the method of circulating nitrogen gas within the reaction system of the reaction apparatus exemplified later is most preferred. Furthermore, the nitrogen source used is not limited to nitrogen gas, but is not particularly limited as long as it is a gas capable of nitriding in the reduction nitriding reaction. Specifically, in addition to nitrogen gas, ammonia gas can also be used. It is also possible to use a mixture of nitrogen gas, ammonia gas, and non-oxidizing gases such as hydrogen, argon, and helium.

[0048] The heating temperature in the reduction nitriding step can be 1500 to 1900°C, preferably 1600 to 1800°C, and more preferably 1650 to 1750°C. By setting the heating temperature within this range, it becomes easy to achieve the average particle size, specific surface area, and oil absorption of the powder within this range.

[0049] The duration of the reduction nitriding process is determined as appropriate, but is, for example, about 2 to 12 hours, and preferably 5 hours or more. By setting the duration within this range, it becomes easier to achieve a compressive fracture strength within that range.

[0050] <Re-firing process> The re-calcination step is a step in which the coarse hexagonal boron nitride powder obtained in the reduction-nitridation step is subjected to a reduction-nitridation reaction again, thereby completely reducing and nitriding any unreacted components in the coarse hexagonal boron nitride powder. In the re-calcination step, the supply of a nitrogen source to the reaction system may be in the same manner as in the reduction-nitridation step.

[0051] The heating temperature in the re-firing process can be 1850 to 2000°C, preferably 1870 to 1970°C, and more preferably 1900 to 1950°C. With such heating temperatures, it is possible to improve the crystallinity and purity of the coarse hexagonal boron nitride powder while preventing the formation of nitrogen defects and yellowing due to carbon doping during firing, thereby obtaining the powder favorably.

[0052] Furthermore, the heating time in the re-firing process is 5 hours or more, preferably 6 hours or more. By setting the heating time within this range, the powder is more easily obtained, the crystallinity and purity of the powder are improved, and the effect of improving thermal conductivity is further enhanced.

[0053] The reduction-nitriding and re-calcination processes described above can be carried out using known reactors capable of controlling the reaction atmosphere. For example, atmosphere-controlled high-temperature furnaces that perform heat treatment by high-frequency induction heating or heater heating can be used, and in addition to batch furnaces, continuous heating furnaces such as pusher-type tunnel furnaces and vertical reactors can also be used.

[0054] <Classification process> The classification process is a process in which the untreated hexagonal boron nitride powder obtained in the re-calcination process is classified under specific conditions using an air-flow classifier. A cylindrical screen classifier is used as the airflow classifier. The cylindrical screen classifier has a plurality of flat blades attached radially with a slight twist angle to the outer circumference of a support disc on a rotor that rotates at high speed, and a cylindrical screen mounted on its outer circumference at a distance that does not come into contact with the blades. The material to be classified is fed into the rotor from one end of the outer circumference of the high-speed rotating rotor, and as the rotor rotates, the material to be classified is uniformly dispersed along the inner surface of the circumference of the cylindrical screen by the action of the blades. Centrifugal force is applied to the material to be classified, and materials finer than the mesh of the cylindrical screen pass through the mesh, while coarse powder remaining on the inner surface of the screen is conveyed by the effect of the twist angle of the blades and discharged from the other end.

[0055] In other words, when the untreated hexagonal boron nitride powder is classified by the cylindrical screen classifier, the product transported to the fine powder side and the coarse foreign matter transported to the coarse powder side are subjected to centrifugal force as described above and pressed against the cylindrical screen, thereby being classified. On the other hand, fibrous foreign matter contained in the untreated hexagonal boron nitride powder is removed to the coarse powder side without being pressed against the cylindrical screen by the vortex created by the multiple flat blades mounted on the high-speed rotating rotor. This makes it possible to remove the fibrous foreign matter, which was difficult with conventional classification methods. The principle is not clear, but because the fibrous foreign matter is fibrous, it has a larger specific surface area compared to the untreated hexagonal boron nitride powder, which is generally spherical, and the specific gravity of carbon fibers, which are the main cause of the fibrous foreign matter, is 1.7~1.8 g / cm³. 3 and untreated hexagonal boron nitride powder (specific gravity: 2.1 g / cm³) 3 It is presumed that this is because, due to its lower specific gravity, it is more susceptible to the effects of airflow, and because of its low specific gravity, it is less affected by the centrifugal force, making it easier to separate from the coarse hexagonal boron nitride powder. The fibrous foreign matter has a major axis of 50 μm or more, but because it is fibrous, it is difficult to remove by classification using sieves, etc. However, it can be removed by airflow classification.

[0056] The rotational speed of the rotor is 1200 to 1800 rpm. By setting the rotational speed within this range, the product conveyed to the fine powder side is less likely to be removed to the coarse powder side, similar to the fibrous foreign matter, and the coarse foreign matter and the fibrous foreign matter can be removed efficiently.

[0057] The mesh opening of the cylindrical screen filter is preferably 85 to 150 μm, and more preferably 105 to 125 μm. By performing airflow classification within this range, fibrous foreign matter and other foreign matter can be efficiently removed without removing coarse aggregated particles with high thermal conductivity.

[0058] <Other processes> The method for producing hexagonal boron nitride powder of the present invention may include steps other than those described above. Such steps are referred to as "other steps" in this specification. Examples of other steps included in the method for producing hexagonal boron nitride powder include a grinding step, an acid washing step, a water washing step, and a drying step.

[0059] The grinding process involves grinding the coarse hexagonal boron nitride powder to adjust it to a predetermined particle size distribution. Grinding is preferably carried out slowly using a jet mill, ball mill, hammer mill, or stone mill type grinder. The particle size distribution may also be adjusted by the aforementioned airflow classification or sieving classification process.

[0060] The acid washing process involves washing the crude hexagonal boron nitride powder with acid to remove boron sources, alkali metal salts, and reaction by-products such as complex oxides that adhere to the crude hexagonal boron nitride powder. In the acid washing process, it is preferable to use a dilute acid such as hydrochloric acid. The acid washing method is not particularly limited and may be acid washing by showering, acid washing by soaking, or acid washing by stirring.

[0061] The water washing step is a step in which the crude hexagonal boron nitride powder is washed with water in order to remove the acid that adhered to the crude hexagonal boron nitride powder in the acid washing step. The water washing method is not particularly limited, and the crude hexagonal boron nitride powder may be washed with water by showering after filtering, or it may be washed with water by soaking.

[0062] The drying process involves drying the prepared crude hexagonal boron nitride powder. The drying method is not particularly limited and may include high-temperature drying or reduced-pressure drying.

[0063] [Resin composition] The hexagonal boron nitride powder of the present invention can be used, for example, as a filler in a resin composition. That is, a resin composition according to one embodiment of the present invention (hereinafter sometimes referred to as "the resin composition") may contain the powder. In such a resin composition, the powder may be used as a filler for mixing with a resin described later for purposes such as improving electrical insulation or imparting thermal conductivity. By filling with the powder, the resin composition has high electrical insulation and thermal conductivity.

[0064] This resin composition can be used in a variety of applications, but it is preferably used to form thermally conductive resin compositions or thermally conductive molded articles for applications such as thermal interface materials such as polymer resin sheets and phase change sheets, organic resin sheets such as heat dissipation tapes, heat dissipation greases, heat dissipation adhesives, and gap fillers, heat dissipation paints such as heat dissipation paints and heat dissipation coatings, heat dissipation resin substrates such as PWB-based resin substrates and CCL-based resin substrates, insulating layers for metal-based substrates such as aluminum-based substrates and copper-based substrates, and encapsulants for power devices.

[0065] Examples of the aforementioned resins include thermoplastic resins such as polyolefins, vinyl chloride resins, methyl methacrylate resins, nylon, and fluororesins; thermosetting resins such as epoxy resins, phenolic resins, urea resins, melamine resins, unsaturated polyester resins, silicon resins, and bismaleimidotriazine resins; and synthetic rubbers.

[0066] Furthermore, this resin composition may optionally contain polymerization initiators, curing agents, polymerization inhibitors, polymerization retarders, coupling agents, plasticizers, ultraviolet absorbers, pigments, dyes, antibacterial agents, and known inorganic fillers other than this powder, such as alumina and aluminum nitride, organic fillers, and organic-inorganic composite fillers.

[0067] [Resin sheet] A resin sheet according to one embodiment of the present invention (hereinafter sometimes referred to as "the present resin sheet") may be composed of the above-mentioned present resin composition. The application of the present resin sheet is not particularly limited, and it can be used, for example, for circuit board applications, insulating layer applications of multilayer printed wiring boards, and the like.

[0068] [Other Applications] The hexagonal boron nitride powder of the present invention can also be used in applications such as raw materials for processed boron nitride products such as cubic boron nitride or boron nitride molded articles, nucleating agents for engineering plastics, phase change materials, solid or liquid thermal interface materials, release agents for molten metal or molten glass molding dies, cosmetics, and raw materials for composite ceramics.

[0069] [Summary] As can be understood from the above description, the present invention includes the following aspects. [1] A hexagonal boron nitride powder comprising hexagonal boron nitride aggregated particles, having an average particle diameter of 30 to 80 μm, a specific surface area of 1.8 to 4.0 m 2 / g, an oil absorption of 55 to 85 ml / 100g, and 15 or less foreign matters with a major axis of 50 μm or more per 1 kg. [2] The hexagonal boron nitride powder according to [1], which has a compressive fracture strength of 1.0 to 5.0 MPa. [3] The hexagonal boron nitride powder according to [1] or [2], wherein the amount of metal impurities is 50 ppm or less. [4] A resin composition obtained by filling the hexagonal boron nitride powder according to any one of [1] to [3]. [5] A resin sheet for electronic components, comprising the resin composition according to [4]. [6] A raw material preparation step of mixing an oxygen-containing boron compound, a carbon source, an oxygen-containing calcium compound and boron carbide to prepare a raw material powder, A reduction nitridation step of heating the raw material powder obtained by the raw material preparation step in a nitrogen atmosphere at a temperature of 1500 to 1900°C for 2 to 12 hours to obtain a crude boron nitride powder, The crude boron nitride powder obtained by the aforementioned nitriding reduction step is reheated in a nitrogen atmosphere at a temperature of 1850-2000°C for 5 hours or more to obtain untreated hexagonal boron nitride powder. A method for producing hexagonal boron nitride powder, comprising a classification step of classifying the untreated hexagonal boron nitride powder obtained by the reheating step using an air jet classifier to obtain hexagonal boron nitride powder. [7] The ratio B / C (elemental ratio) of the B-equivalent mass of the oxygen-containing boron compound to the C-equivalent mass of the carbon source is 0.81 to 1.10. For a total of 100 parts by mass of the oxygenated boron compound (calculated as B2O3 on a B basis) and the carbon source (calculated as C), the oxygenated calcium compound is present in an amount of 4.0 to 18.0 parts by mass in terms of CaO on a Ca basis. A method for producing hexagonal boron nitride powder according to [6], wherein the boron carbide is 10 to 30 parts by mass per 100 parts by mass of the total amount of the oxygenated boron compound, the carbon source, and the oxygenated calcium compound, each in terms of B2O3, C, and CaO. [Examples]

[0070] The present invention will be further illustrated by the following examples, but the invention is not limited thereto. The values ​​in the examples and comparative examples were measured by the following methods.

[0071] (1) Average particle size (D 50 ) The particle size was measured using the laser diffraction method with a laser diffraction / scattering particle size analyzer MT3000 (Microtrac-Bell). Specifically, 0.1g of hexagonal boron nitride powder was placed in the mixing tank attached to the device, which was filled with 50cc of ethanol, and ultrasonically dispersed for 20 seconds at an output of 40W. The sample used for measurement was the average particle size (D) based on volume. 50 ) was calculated.

[0072] (2) Specific surface area The specific surface area of ​​hexagonal boron nitride powder in both the examples and comparative examples was measured using a Micromeritics FlowSorb III 2310.

[0073] (3) Oil absorption amount For both the examples and comparative examples, measurements were performed in accordance with JIS-K6217-4 using hexagonal boron nitride powder and dibutyl phthalate (DBP) as the solvent. A DBP drop-torque curve was obtained with the x-axis representing DBP drop volume (mL / 100g powder) and the y-axis representing torque (Nm). Specifically, 20g of powder was placed in a mixing chamber, and DBP was added dropwise at a rate of 4.0 mL / min while stirring at 125 rpm with a rotor, and the torque was measured over time. The DBP drop-torque curve was created from these measurement results. An oil absorption meter S-500 (manufactured by Asahi Research Institute Co., Ltd.) was used as the measuring device. DBP was prepared using a special grade reagent (distributor code 021-06936) manufactured by Wako Pure Chemical Industries, Ltd.

[0074] (4) Content of foreign matter with a major diameter of 50 μm or more The number of foreign particles with a major axis of 50 μm or larger contained in 1 kg of hexagonal boron nitride powder prepared in each of Examples 1-4 and Comparative Examples 1-3 was measured by the following method.

[0075] A resin sheet was prepared using the hexagonal boron nitride powder and epoxy resin, and inspected visually from the top of the sheet using a camera while irradiating it with light from the bottom. Specifically, 50 g of hexagonal boron nitride powder was mixed with 14.4 g of liquid curable epoxy resin (JER828, manufactured by Mitsubishi Chemical, bisphenol A type epoxy resin, epoxy resin 184-194 g / eq) and 40 g of cyclohexanone as a solvent, and then 3.60 g of epoxy resin curing agent (JERcureW, manufactured by Mitsubishi Chemical, modified aromatic amine, amine value 623-639) was added and mixed using a rotary-orbit mixer (Mazelstar KK-250S, manufactured by Kurabo Industries Ltd.) to prepare a curable composition. The obtained curable composition was coated onto a release PET film (PET50×1-FSC6, manufactured by Nipper, 50 μm thick) using an automatic coating device (PI-1210, manufactured by Tester Industries Co., Ltd.) with a bird-type applicator to a film thickness of 250 μm. After air-drying the coated film for 10 minutes, it was vacuum-dried in a vacuum dryer at 80°C for 60 minutes to obtain a plate-shaped molded body. Next, the obtained plate-shaped molded body was sandwiched between two 100 × 100 mm copper foils and pressed under reduced pressure at 100°C and a press pressure of 10 MPa for 3 minutes. The temperature was then raised to 150°C and pressed under reduced pressure for 60 minutes to cure it, and then the copper foils were peeled off to produce a white resin sheet with a thickness of approximately 80 μm. Twenty of these resin sheets were prepared and placed on top of a backlighting device. While irradiating the resin sheets with white light from below, the appearance of the resin sheets was observed using an FA image processing device (Panasonic IMAGECHECKAR PV200). The number of foreign objects with a major axis of 50 μm or larger contained in 1 kg of hexagonal boron nitride powder was then measured by visual inspection.

[0076] (5) Measurement of compressive failure strength Compression tests were conducted using a microcompression testing machine MCT-510 manufactured by Shimadzu Corporation to measure the compressive fracture strength of hexagonal boron nitride powder. The compression test was performed by applying a load to the sample with an indenter, showing the graph of test force (mN)-displacement (μm) at which the sample fractured, defining the fracture point P as the test force (mN) at which the displacement became constant, and calculating the fracture strength (MPa) using the following formula. Breaking strength (MPa) = (2.48P) / (3.14d) 2 ) (d: average particle size) The measurement conditions were as follows: indenter = FLAT200 (200 μm flat plate indenter), test force = 50 (mN), loading rate = 4.8420 (mN / sec), and load holding time = 5 (sec). Approximately 100 aggregates were selected from the obtained hexagonal boron nitride powder, their compressive fracture strength was measured, and the average value was calculated.

[0077] (6) Amount of metal impurities The amount of metal impurities was measured using an ICP emission spectrometer (Thermo Fisher Scientific K.K.: ICAP6500). For details, 50 g of a 0.5 mol / L sulfuric acid aqueous solution and 2 g of hexagonal boron nitride powder were added to a 50 mL iBoy container, and the mixture was shaken for 1 minute while adjusting the temperature of the solution to 25°C. After standing for 120 minutes, the amounts of Fe, Ca, Al, and Si in the resulting solution were analyzed using an ICP emission spectrometer. From the obtained measurement results, the amounts of Fe, Ca, Al, and Si per unit mass of hexagonal boron nitride powder were calculated and summed.

[0078] (7) Evaluation of thermal conductivity, dielectric strength, and reliability Hexagonal boron nitride powder was packed into epoxy resin to prepare resin sheets for both the examples and comparative examples, and their thermal conductivity and dielectric strength were evaluated. Specifically, a base resin mixture was prepared with 100 parts by mass of epoxy resin (JER828, manufactured by Mitsubishi Chemical Corporation), 5 parts by mass of a curing agent (imidazole-based curing agent, Curesol 2E4MZ, manufactured by Shikoku Chemicals Co., Ltd.), and 210 parts by mass of a solvent, methyl ethyl ketone. Next, the base resin mixture and hexagonal boron nitride powder were mixed so that the ratio of epoxy resin to hexagonal boron nitride powder was 30% by volume of epoxy resin and 70% by volume of hexagonal boron nitride powder, and the mixture was stirred in a rotation / revolution mixer (MAZERUSTAR, manufactured by Kurabo Industries Ltd.) to obtain varnish. This varnish was applied to copper foil to a thickness of approximately 250-300 μm using a PI-1210 automatic coating machine manufactured by Tester Industries Co., Ltd., and after drying, it was cured under reduced pressure, at a temperature of 200°C, a pressure of 5 MPa, and a holding time of 30 minutes to produce a resin sheet with a thickness of 200 μm. The resin sheet was analyzed using a thermal wave thermal analyzer, and its thermal conductivity was calculated. The calculated thermal conductivity was evaluated according to the following criteria. A thermal conductivity evaluation of "◎" or "〇" indicates that the resin sheet has excellent thermal conductivity. ◎: 18W / m·K<Thermal conductivity> 〇:17W / m·K<thermal conductivity≦18W / m·K △: 15 W / m·K < Thermal conductivity ≤ 17 W / m·K ×: Thermal conductivity ≤ 15 W / m·K Furthermore, the dielectric strength of each resin sheet was measured using an dielectric strength tester (manufactured by Tama Densoku Co., Ltd.). The average of the dielectric strength measured for 20 sheets was evaluated according to the following criteria. If the dielectric strength evaluation is "◎" or "〇", it can be said that the dielectric strength of the resin sheet is excellent. ◎: 55KV / mm < Dielectric strength ○: 53KV / mm < Dielectric strength ≤ 55KV / mm △: 51KV / mm < Dielectric strength ≤ 53KV / mm ×: Dielectric strength ≤ 51KV / mm² Furthermore, as an indicator of the reliability of the dielectric strength, the lowest value among the data obtained when measuring the dielectric strength was also evaluated according to the following criteria. If the evaluation of the lowest dielectric strength is "◎" or "〇", it can be said that the reliability of the dielectric strength of the resin sheet is excellent. ◎: 45KV / mm < Dielectric strength ○: 43KV / mm < Dielectric strength ≤ 45KV / mm △: 41KV / mm < Dielectric strength ≤ 43KV / mm ×: Dielectric strength ≤ 41KV / mm²

[0079] (Example 1) As a raw material powder, 2605g of a mixture containing 1410g of boron oxide, 520g of carbon black, 300g of calcium oxide, and 375g of boron carbide was mixed using a ball mill to obtain the raw material powder. The aforementioned raw material powder was subjected to reductive nitriding treatment using a graphite Tamman furnace, held at a maximum temperature of 1600°C for 6 hours under a nitrogen gas atmosphere, to obtain crude hexagonal boron nitride powder. After crushing the aforementioned crude hexagonal boron nitride, the crude hexagonal boron nitride powder was placed in a container, five times the amount of hydrochloric acid (7% by mass HCl) was added, and the mixture was stirred at 700 rpm for 24 hours to perform an acid pickling treatment. After this acid pickling treatment, the acid was filtered, and the filtered crude hexagonal boron nitride powder was dispersed in the same amount of pure water as the acid used, and filtered again. This operation was repeated five times, and then the mixture was vacuum dried at 200°C for 6 hours. The aforementioned crude hexagonal boron nitride powder was re-calcined in a graphite Tamman furnace under a nitrogen gas atmosphere at a maximum temperature of 1940°C for 6 hours to obtain untreated hexagonal boron nitride powder. The aforementioned untreated hexagonal boron nitride powder was classified using a vibrating sieve with a mesh size of 106 μm, and then subjected to airflow classification using a turbo screener (manufactured by Freund Turbo Co., Ltd.) with a mesh size of 85 μm, a rotor rotation speed of 1400 rpm, and a processing speed of 30 kg / h.

[0080] (Example 2) Except for changing the mesh size of the turbo screener to 150 μm, the same procedure as in Example 1 was performed to obtain the hexagonal boron nitride powder of Example 2.

[0081] (Example 3) Except for changing the mesh size of the turbo screener to 105 μm, the same procedure as in Example 1 was performed to obtain the hexagonal boron nitride powder of Example 3.

[0082] (Example 4) As a raw material powder, 2590g of a mixture containing 1410g of boron oxide, 560g of carbon black, 320g of calcium oxide, and 300g of boron carbide was mixed using a ball mill to obtain the raw material powder. The aforementioned raw material powder was subjected to reductive nitriding treatment using a graphite Tamman furnace, held at a maximum temperature of 1750°C for 2 hours under a nitrogen gas atmosphere, to obtain crude hexagonal boron nitride powder. After crushing the aforementioned crude hexagonal boron nitride, the crude hexagonal boron nitride powder was placed in a container, five times the amount of hydrochloric acid (7% by mass HCl) was added, and the mixture was stirred at 700 rpm for 24 hours to perform an acid pickling treatment. After this acid pickling treatment, the acid was filtered, and the filtered crude hexagonal boron nitride powder was dispersed in the same amount of pure water as the acid used, and filtered again. This operation was repeated five times, and then the mixture was vacuum dried at 200°C for 6 hours.

[0083] Coarse hexagonal boron nitride powder, φ145mm, thickness 10mm, mesh opening 5mm x 8mm, 54cm 2Magnetic separation was performed using an electromagnetic sieving device consisting of 40 stacked screens, each having a magnetic pole area and magnetized to 1.6T. Magnetic separation was carried out at a processing rate of 15 kg / h. The crude hexagonal boron nitride powder after magnetic separation was heated in an air atmosphere at an oxidation temperature of 600°C for 5 hours to oxidize the organic components. The crude hexagonal boron nitride powder was placed in a container, five times the amount of hydrochloric acid (7 mass% HCl) was added, and the mixture was stirred at a rotation speed of 700 rpm for 24 hours to perform an acid pickling treatment. After this acid pickling treatment, the acid was filtered, and the filtered crude hexagonal boron nitride powder was dispersed in the same amount of pure water as the acid used, and filtered again. This operation was repeated 5 times, and then the powder was vacuum dried at 200°C for 6 hours. The crude hexagonal boron nitride powder obtained after drying was re-calcined in a graphite Tamman furnace under a nitrogen gas atmosphere at a maximum temperature of 1900°C for 6 hours to obtain untreated hexagonal boron nitride powder.

[0084] The untreated hexagonal boron nitride powder was classified using a vibrating sieve with a mesh size of 106 μm. From the resulting hexagonal boron nitride powder, colored foreign matter particles with a brightness of 110 or less and a particle size of 50 μm or larger were removed by suction using a powder foreign matter inspection and removal machine (Nisshin Kasei Co., Ltd., PGS-R2). Then, airflow classification was performed using a turbo screener with a mesh size of 105 μm and a processing speed of 30 kg / h.

[0085] (Example 5) Except for changing the rotor speed of the turbo cleaner to 1800 rpm, the same procedure as in Example 2 was performed to obtain the hexagonal boron nitride powder of Example 5.

[0086] (Comparative Example 1) The same procedure as in Example 1 was followed to obtain the hexagonal boron nitride powder of Comparative Example 1, except that classification using a turbo screener was not performed.

[0087] (Comparative Example 2) Comparative Example 2 was obtained by performing the same procedure as in Example 1, except that instead of using a turbo screener for airflow classification at a mesh size of 85 μm and a processing speed of 30 kg / h, a gravity-drop type vibrating classifier was used for classification at a mesh size of 85 μm and a processing speed of 30 kg / h.

[0088] (Comparative Example 3) The same procedure as in Example 4 was followed, except that classification using a turbo screener was not performed, to obtain the hexagonal boron nitride powder of Comparative Example 3. Comparative Example 3 is a reproduction of Example 6 of the aforementioned Patent Document 3.

[0089] (result) The hexagonal boron nitride powders obtained in Examples 1-5 and Comparative Examples 1-3 were evaluated using the methods described above. Furthermore, resin sheets were prepared and evaluated using the hexagonal boron nitride powders according to the methods described in (4) and (7) above. The results are shown in Tables 1 and 2 below.

[0090] [Table 1]

[0091] [Table 2]

Claims

1. It contains hexagonal boron nitride aggregated particles, with an average particle size of 30 to 80 μm and a specific surface area of ​​1.8 to 4.0 m². 2 Hexagonal boron nitride powder with a concentration of 55-85 ml / g, an oil absorption capacity of 55-85 ml / 100 g, and fewer than 15 foreign particles per kg with a major diameter of 50 μm or more.

2. The hexagonal boron nitride powder according to claim 1, wherein the compressive fracture strength is 1.0 to 5.0 MPa.

3. The hexagonal boron nitride powder according to claim 1, wherein the amount of metal impurities is 50 ppm or less.

4. A resin composition filled with hexagonal boron nitride powder according to any one of claims 1 to 3.

5. A resin sheet for an electronic component made from the resin composition described in claim 4.

6. A raw material preparation step involves mixing an oxygenated boron compound, a carbon source, an oxygenated calcium compound, and boron carbide to prepare a raw material powder. A reduction nitriding step is performed in which the raw material powder obtained in the raw material preparation step is heated in a nitrogen atmosphere at a temperature of 1500 to 1800°C for 2 to 12 hours to obtain crude boron nitride powder. A reheating step is performed to obtain untreated hexagonal boron nitride powder by reheating the crude boron nitride powder obtained by the aforementioned nitriding reduction step at a temperature of 1850 to 2000°C for 5 hours or more under a nitrogen atmosphere. A method for producing hexagonal boron nitride powder, comprising a classification step of classifying the untreated hexagonal boron nitride powder obtained by the reheating step using a gravity-feed classifier and an air-flow classifier to obtain hexagonal boron nitride powder.

7. The ratio B / C (elemental ratio) of the B-equivalent mass of the oxygen-containing boron compound to the C-equivalent mass of the carbon source is 0.81 to 1.

10. B of the aforementioned oxygen-containing boron compound, based on B standard 2 O 3 For a total of 100 parts by mass of the converted mass and the C-equivalent mass of the carbon source, the oxygen-containing calcium compound is 4.0 to 18.0 parts by mass in terms of CaO on a Ca basis. The oxygenated boron compound, the carbon source, and the oxygenated calcium compound are each B. 2 O 3 A method for producing hexagonal boron nitride powder according to claim 6, wherein the boron carbide is 10 to 30 parts by mass with respect to 100 parts by mass of the total amount of C and CaO equivalent mass.

Citation Information

Patent Citations

  • Hexagonal boron nitride powder

    JP7588527B2

  • Hexagonal boron nitride powder and method for producing sintered body

    WO2022071245A1

  • Method for producing hexagonal boron nitride powder, and hexagonal boron nitride powder

    WO2024225208A1